A Combined Model of Global Cultivated Area Change and Prediction for Future: 1961–2020. (16th September 2013) - Wang, Cheng-Jun; Fei, Xi-Min
Abstract : As a basic condition for food safety, cultivated area fluctuates in recent years. So, it has important political and economical significance to understand the future change trend of global cultivated area. Based on historical data in the past 50 years, deterministic time series analysis model, random time series analysis model, and combined model were established by using time series analysis method. By comparison, the combined model has the highest fitting and prediction accuracy, and it is suitable for the prediction of global cultivated area change trend. The global cultivated area will rise slightly in fluctuation in the near future driven by a combination of deterministic factors and random factors.